UK Head and neck cancer surgical capacity during the second wave of the COVID—19 pandemic: Have we learned the lessons? COVIDSurg collaborative - Shaw, R (Wiley, 2021)
Objectives The aim of this study was to evaluate the differences in surgical capacity for head and neck cancer in the UK between the first wave (March-June 2020) and the current wave (Jan-Feb 2021) of the COVID-19 pandemic.